2016
DOI: 10.1073/pnas.1518707113
|View full text |Cite
|
Sign up to set email alerts
|

Functions for diverse metabolic activities in heterochromatin

Abstract: Growing evidence demonstrates that metabolism and chromatin dynamics are not separate processes but that they functionally intersect in many ways. For example, the lysine biosynthetic enzyme homocitrate synthase was recently shown to have unexpected functions in DNA damage repair, raising the question of whether other amino acid metabolic enzymes participate in chromatin regulation. Using an in silico screen combined with reporter assays, we discovered that a diverse range of metabolic enzymes function in hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…Furthermore, the binding scores of some metabolic enzymes changed upon treatment with HU (Supplementary Table 2), indicating that their interaction with chromatin is not constitutive. Indeed, there is a growing body of evidence that enzymes in the cytoplasm might have moonlighting functions in the nucleus, for example by local supply of co-factors of histone modifying enzymes 19,46,[51][52][53][54] . Alternatively, the interaction with chromatin could somehow influence the activity of metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the binding scores of some metabolic enzymes changed upon treatment with HU (Supplementary Table 2), indicating that their interaction with chromatin is not constitutive. Indeed, there is a growing body of evidence that enzymes in the cytoplasm might have moonlighting functions in the nucleus, for example by local supply of co-factors of histone modifying enzymes 19,46,[51][52][53][54] . Alternatively, the interaction with chromatin could somehow influence the activity of metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…RNA processing events such as capping, splicing, cleavage, and polyadenylation are all processes known to occur in close conjunction with RNA transcription and hence in proximity to DNA 17 , providing an explanation for the recovery of barcodes associated with RNA processing proteins. The presence of factors involved in cellular metabolism cannot be explained by general associations with transcription, although recent studies have suggested various roles of metabolic enzymes in the nucleus 4,[18][19] (and see discussion). Given the fact that some of these factors are known to be highly expressed, we investigated the possibility that their chromatin interactions were determined by protein abundance.…”
Section: Epi-decoder Identifies Many Chromatin-associated Factorsmentioning
confidence: 99%
“…This novel epigenetic regulatory mechanism is actually an interesting research topic, as reflected in a recent review [38], and H3 modifications have been connected to different stress responses, including OS and lifespan in C. elegans and Drosophila [39,40]. Other amino acid metabolic enzymes could participate in chromatin regulation [41]. This is the case of one protein that was differently expressed in our study: Gdh1.…”
Section: Discussionmentioning
confidence: 56%
“…Gdh3p was considered the molecular target of ebselen which ceased NADP-GDH activity through the formation of selenyl-sulfide bonds with cysteine residues. It was also observed that the NADP-GDH inactivation might had a critical function in the proteolysis of H3 histone in yeast [ 38 40 ], as discussed below.…”
Section: The Gdh Pathway In S Cerevisiaementioning
confidence: 99%
“…The role of Gdh1p in transcriptional silencing was found to be crucial through the proteolysis of H3 histone in yeast (“H3-clipping” in the N-tail) [ 40 ]. This effect has been described previously in animal tissues [ 39 , 67 ].…”
Section: Additional Roles Of the Gdh Pathwaymentioning
confidence: 99%